2005
DOI: 10.1007/s11103-005-0698-4
|View full text |Cite
|
Sign up to set email alerts
|

ASYMMETRIC LEAVES2-LIKE1gene, a member of the AS2/LOB family, controls proximal?distal patterning in Arabidopsis petals

Abstract: The formation and the development of the floral organs require an intercalate expression of organ-specific genes. At the same time, meristem-specific genes are repressed to complete the differentiation of the organs in the floral whorls. In an Arabidopsis activation tagging population, a mutant affected in inflorescence architecture was identified. This gain-of-function mutant, designated downwards siliques1 (dsl1-D), has shorter internodes and the lateral organs such as flowers are bending downwards, similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
89
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(94 citation statements)
references
References 52 publications
5
89
0
Order By: Relevance
“…However, several loss-of-function mutants of rice and maize LBD genes have been reported to evidence clear phenotypes (Inukai et al, 2005;Liu et al, 2005;Bortiri et al, 2006;Evans, 2007;Taramino et al, 2007). The ectopic expression of several LBD genes, as wild type or as proteins fused to a transcriptional repression domain, yielded morphological phenotypes, provid- ing clues to the biological functions of these LBD genes (Shuai et al, 2002;Chalfun-Junior et al, 2005;Borghi et al, 2007;Okushima et al, 2007). For example, the overexpression of LBD16 or LBD29 induced lateral root formation in the absence of ARF7 and ARF19, and the dominant repression of LBD16 activity inhibited lateral root formation; these findings suggest that these LBDs function downstream of ARF7-and ARF19-dependent auxin signaling in lateral root formation (Okushima et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, several loss-of-function mutants of rice and maize LBD genes have been reported to evidence clear phenotypes (Inukai et al, 2005;Liu et al, 2005;Bortiri et al, 2006;Evans, 2007;Taramino et al, 2007). The ectopic expression of several LBD genes, as wild type or as proteins fused to a transcriptional repression domain, yielded morphological phenotypes, provid- ing clues to the biological functions of these LBD genes (Shuai et al, 2002;Chalfun-Junior et al, 2005;Borghi et al, 2007;Okushima et al, 2007). For example, the overexpression of LBD16 or LBD29 induced lateral root formation in the absence of ARF7 and ARF19, and the dominant repression of LBD16 activity inhibited lateral root formation; these findings suggest that these LBDs function downstream of ARF7-and ARF19-dependent auxin signaling in lateral root formation (Okushima et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The gain-of-function mutants of LBD36/ASL1, designated downwards siliques1, showed shorter internodes and downward lateral organs such as flowers (Chalfun-Junior et al, 2005). Although the lbd36 loss-of-function mutants did not show morphological phenotypes, the analysis of lbd36 as2 double mutants showed that these two members act redundantly to control cell fate determination in the petals.…”
mentioning
confidence: 99%
“…SlCYP707A1 coding region was recombined between the CauliXower Mosaic Virus 35S promoter in the pGD625 vector (Chalfun-Junior et al 2005) and the NOPALINE SYNTHASE terminator. Water stress experiment…”
Section: Overexpression Linesmentioning
confidence: 99%
“…Core CC genes are depicted in purple. Self-regulation and homodimerization were removed from the network figure. to the cluster based on experimental PPI data (Chalfun-Junior et al, 2005;Phelps-Durr et al, 2005).…”
Section: The Integrated Arabidopsis Text and Interaction Networkmentioning
confidence: 99%